Lentaria deqinensis (Lentariaceae, Gomphales), a new species from southwestern China - Li, Mei-Jia; Deng, Peng-Tao; Liu, Xiang-Fen; Zhang, Ping (Phytotaxa, 2025)
Lentaria Corner is a widespread saprophytic genus in Lentariaceae, which plays important roles as a decomposer to promote the nutrient cycle and maintain ecosystem stability. In this study, Lentaria deqinensis is described as a new species that grows under the Picea in Yunnan Province. Molecular phylogenetic analysis of concatenated internal transcribed spacer (ITS) and nuclear ribosomal RNA large subunit (nrLSU) sequence data resolved L. deqinensis as a well-supported distinct lineage within the Lentaria clade. Lentaria deqinensis formed a sister group with L. patouillardii with PP 1, and BS 100% statistical support. In morphology, L. deqinensis differs from L. patouillardii in having more strongly acute and white branch apices, semitransparent branches, and larger basidiospores ((8.0–)8.1–10.4(–11.3) × (2.0–)2.1–3.5(–4.0) μm vs. 7–9 × 2–3 μm). A description, illustrations, and phylogenetic analysis results of the proposed species are presented. In addition, a key to the known Lentaria species in China is provided.